Perceptions of Effective E-moderation: A Tutors Viewpoint - Packham, Gary; Jones, Paul; Miller, Christopher; Thomas, Brychan (Proceedings of the International Conference on Networked Learning, 2004)
This paper examines tutor perceptions of effective e-moderation. The study investigates the on-line BA Enterprise programme, part of the E-College Wales initiative initiated by the University of Glamorgan. The course is supported by “Blackboard” software utilising synchronous and asynchronous communication mechanisms. The methodology involved semi-structured interviews with 35 e-moderators from the University and partner colleges. Analysis of the results revealed that effective e-moderators required specific qualities, characteristics and organisational skills. Effective communication and responsive feedback were judged to be the most critical activities. This research can be utilised by e-learning providers to identify effective and efficient e-moderator practices.